2015
DOI: 10.7899/jce-14-20
|View full text |Cite
|
Sign up to set email alerts
|

Participation strategies and student performance: An undergraduate health science retrospective study

Abstract: Objective: This research explores participatory evidence-based teaching methods in a health science course to see if a relationship emerged between the level of student participation and course performance, the type of participation and course performance, or the amount of participation and course performance and level of demonstrated learning. Methods: Level of student participation was dichotomous (100% or ,100%), and differences between groups on a knowledge test were compared using an unpaired t test. Type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Active participation of students in preparing and giving talks, and having direct contact with adolescents, was the difference between both groups (T2 inter-T2 control). These results are in line with other studies which have demonstrated that active learning obtains leads to results and produces higher long-term retention knowledge in students [19][20][21] . Traditional approaches produce short-term retention of course content because they do not include elaboration.…”
Section: Discussionsupporting
confidence: 93%
“…Active participation of students in preparing and giving talks, and having direct contact with adolescents, was the difference between both groups (T2 inter-T2 control). These results are in line with other studies which have demonstrated that active learning obtains leads to results and produces higher long-term retention knowledge in students [19][20][21] . Traditional approaches produce short-term retention of course content because they do not include elaboration.…”
Section: Discussionsupporting
confidence: 93%
“…Bolden et al (2019) showed location matters when delivering the same material to two groups of students, one in a smaller classroom and one in a large lecture hall. Students in the smaller classroom scored themselves higher in meaningful processing and active participation, which includes engaging with the readings, writings, discussions, or creating and problem solving (Starmer et al, 2015). Students in the larger classroom scored themselves higher in a better overall understanding of the material including having more focused attention, a deeper processing of material, and more advanced learning.…”
Section: Discussionmentioning
confidence: 99%
“…They corresponded to Starmer et al (2015) regarding the importance of active course participation and teacher-student interaction satisfaction in the learning outcome of course satisfaction in m-learning (Baker, 1999;Buriel, 1983;Hughes et al, 2001).…”
Section: The Impact Of Learning Processes On Learning Outcome Of Diffmentioning
confidence: 99%
“…With adequate spontaneous talking or question-asking in class, facilitated by functions of mlearning, but not necessarily face-to-face, learners' active course participation can increase their satisfaction toward teacher's teaching because of the good interaction with teachers (Cazden, 1986;Mehan, 1980). They may also feel satisfaction toward their peers when the different forms of interaction enabled by m-learning in class satisfies their expectations among peers (Cazden, 1986;Mehan, 1980;Starmer, Duquette, & Howard, 2015).…”
Section: The Impact Of Learning Processes On Learning Outcomementioning
confidence: 99%